The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2dt02038f
|View full text |Cite
|
Sign up to set email alerts
|

Pb3SBrI3: the first Pb-based chalcohalide with multiple halogens features a unique two-dimensional structure composed of diverse Pb-centered polyhedra

Abstract: Chalcohalides are attractive multifunctional material candidates due to their diverse crystal structures and the merits fused from chalcogenides and halides. Here, we successfully synthesized a new Pb-based chalcohalide with multiple-halogens,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…However, other Pb atoms contribute only at locations far from the Fermi level, proving that they have an inert stereochemically active lone pair effect (Figure S8). Moreover, Pb(2) atoms in 1 and Pb(3) atoms in 2 are arranged at acute angles along the b axis. This arrangement makes Pb(2) and Pb(3) lone pair electron activities superposition, which is helpful to improving birefringence .…”
mentioning
confidence: 99%
“…However, other Pb atoms contribute only at locations far from the Fermi level, proving that they have an inert stereochemically active lone pair effect (Figure S8). Moreover, Pb(2) atoms in 1 and Pb(3) atoms in 2 are arranged at acute angles along the b axis. This arrangement makes Pb(2) and Pb(3) lone pair electron activities superposition, which is helpful to improving birefringence .…”
mentioning
confidence: 99%
“…Tang et al first reported synthesis of a multiple-halogen-based 2D Pb 3 SBrI 3 chalcohalide through a facile hydrothermal approach. 177 Traditional synthetic methods such as melt/vapor-phase growth, sonochemical, microwave, as well as solvothermal methods were employed for the synthesis of chalcohalide NCs, but these mostly led to poorly defined morphologies. To overcome these issues, Li and co-workers adopted a facile colloidal approach for the synthesis of highly uniform singlecrystalline Bi 19 S 27 Br 3 nanowires (NWs) with a mean diameter of ∼9 nm and tunable lengths in the range of 0.15−2 μm in the presence of foreign metal ions, Al 3+ .…”
Section: ■ Syntheses and Crystal Structures Of Reported Chalcohalide ...mentioning
confidence: 99%
“…Hydrothermal approaches are not restricted to the synthesis of heavy pnictogen chalco­halides; they are also applicable for the synthesis of Pb-based chalco­halide materials. Tang et al first reported synthesis of a multiple-halogen-based 2D Pb 3 SBrI 3 chalco­halide through a facile hydrothermal approach …”
Section: Syntheses and Crystal Structures Of Reported Chalcohalide Ma...mentioning
confidence: 99%
“…The combination of two or more kinds of anion groups to design compounds with interesting structure types is a favorable and fruitful route. 1–32 These new crystals may synergize the properties of multiple anions and can be potential candidates in some application fields including birefringence, nonlinear optics, fluorescence, and catalysis. Based on the structure performance relationship, many research systems focusing on optical performance have been developed in recent years.…”
Section: Introductionmentioning
confidence: 99%